Sosialisasi dan Dukungan Kepada UMKM dalam Pembuatan Nomor Induk Berusaha (NIB) Untuk Pengembangan UMKM di Dusun Pudo Desa Mojosarirejo - Agus Sunaryo; Tatra Prayogi Hermawan; Cantika Ayu Martaviana; Andre Bagus Pratama; Putri Maulidya; Yordan Nagara Yannot Tamma; Amash Titahillah; Amelia Maulindah; Ajeng Savily Aprilleoni; Vinanda Ayu Febryana; Alfan Dwi Nurrohman; Abdillah Alif Alwi; Nova Fitria Lilian; Denis Shevira; Bagas Cahya Pratama; Bagus Arya Walanda; Bakhrul Alam Umarok; Bima Satria Negara; Bunga Nur Fadilah; Dafid Arya Pratama; Dedi Rianto; Angga Pradana Putra; Khalimatun Nisa; Mochammad Abdul Azis (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
Micro, small and medium enterprises or MSMEs are an activity to encourage community economic growth. Pudo Hamlet is one of the hamlets in Mojosarirejo Village, Kemlagi District, Mojokerto Regency which has many business actors. However, most MSMEs players do not understand the importance of the legality of a business. The legality of the business itself is in the form of a Business Identification Number (NIB), because some people understand that processing business permits and legality is very complicated and time consuming. Business Identification Number (NIB) now plays an important role in business management. Therefore, it is necessary to carry out socialization and also provide assistance to the community regarding the importance of the Business Identification Number (NIB) as a form of business legality. The method used in this activity is socialization and assistance which is carried out in three stages, including collecting data on the potential of MSME actors, delivering material, and assistance with registering Business Identification Numbers (NIB). With socialization and assistance, we hope that MSMEs in Pudo Hamlet will have a business legality certificate.